Charles Nicoll Bancker correspondence - Bancker, Charles Nicoll, 1778-1869.
Correspondence addressed to Bancker primarily from his father-in-law, John Teackle, and brother-in-law, Littleton Dennis Teackle, as well as other members of the Teackle family of Maryland. Pertains to family and business matters and documents national economic and political issues related to family's interests in banking, commerce, and shipbuilding. Correspondents discuss conversations with various prominent United States government officials and several British ministers; views of Congress concerning U.S. Secretary of the Treasury Albert Gallatin; British Orders in Council relating to trade with the United States; the embargo of 1807; the Non-Intercourse Act (1809); rechartering of the United States Bank (1811); the anti-embargo stance of the Federal Republican editor resulting in the sacking and burning of his offices in Baltimore, Md. (1812); the War of 1812; and the Hartford Convention and the Treaty of Ghent (1814).
Merchant of Philadelphia, Pa.
Collection material in English.
Keywords: Gallatin, Albert, -- 1761-1849.; Teackle, John -- Correspondence; Teackle, Littleton Dennis, -- 1777-1850 -- Correspondence; Teackle family; Bank of the United States (1791-1811); Federal Republican & commercial gazette; Great Britain. -- 1814 December 24.; Banks and banking -- Maryland; Embargo, 1807-1809.; Shipbuilding -- Maryland; Maryland -- Commerce; Baltimore (Md.) -- History -- War of 1812.; Maryland -- Social life and customs; United States -- Commerce -- Great Britain; Great Britain -- Commerce -- United States; United States -- Commerce -- History -- 19th century; United States -- Economic policy -- To 1933.; United States -- Foreign relations -- 1783-1865.; United States -- Foreign relations -- 1812-1815.; United States -- History -- 1783-1865.; United States -- History -- War of 1812.; United States -- Politics and government -- 1783-1865.; Merchants